Physicochemical and Enzymatic Soil Properties Influenced by Cropping of Primary Wheat under Organic and Conventional Farming Systems - Joanna Lemanowicz (Agronomy, 2020)
The aim of the study was to assess the content of total organic carbon (TOC), macronutrients (P, K, and Mg), and glomalin (easily extractable glomalin-related soil protein (EEGRSP)) in soil, micronutrients (Zn and Cu) in soil and wheat, and the number of insects on plots in an organic (OF) and a conventional farming (CF) system, all against the background of alkaline phosphatase (AlP) and acid phosphatase (AcP) activity. The experimental design included two spring wheat species, Triticum sphaerococcum Percival and Triticum persicum Vavilov, and three sowing densities (grains m−2): 400, 500, 600. Statistical analysis (ANOVA, η2 effect size) showed significant variation in parameters under the influence of experimental factors. In the duration of the field experiment, TOC content in soil had decreased by 61% compared to the content before starting the experiment. The contents of P, K, and Mg and activity of AlP and AcP were higher in soil under T. sphaerococcum. With a sowing density of 600 grains m−2 under OF and CF, the significantly lowest macronutrient content and the highest AlP and AcP activity were found. The parameters tested (TOC, EEGRSP, P, K, Mg, TZn, TCu, AZn, CU in plant, AlP, AcP) were higher under the CF than under the OF system. The experimental factors (spring wheat species and number of germinating grains) were demonstrated to influence the content of the forms of both microelements in soil and plants. In CF, more content in the amount of Zn and Cu was found than in OF. But the content they had did not exceed the standards set for arable soils. Both wheat species had a significant impact on the concentration of glomalin in the soil from the fields cultivated in the OF system. In CF, a significant difference was caused by sowing density and by interaction between wheat species and sowing density. Insects preferred plants grown in the OF system compared to CF. Regardless of cultivation system, the number of insects was greater on the plots of T. sphaerococcum than on plots of T. persicum. There were more insects at higher sowing densities in plants grown in the OF system only.